Augmented Reality Sebagai Sarana Pengenalan Mahasiswa Informatika Udayana - Jaya, I Gede Wilantara; Suhartana, I Ketut Gede (Jurnal Nasional Teknologi Informasi dan Aplikasnya; Vol 1 No 1 (2022): JNATIA Vol. 1, No. 1, November 2022, 2022)
ID cards are very important to have as identification of the owner. At Udayana University, every student has a KTM (Kartu Tanda Mahasiswa). KTM is just an identity that is general in nature and incomplete. Here the author wants to apply technology that combines virtual objects in a real 3-dimensional environment, namely Augmented Reality technology as a medium for introducing students to the Udayana Informatics Study Program. The use of Augmented Reality technology can be used to provide information in 3-dimensional form so that it becomes more interesting through smartphones. Through the creation of Augmented Reality applications for the introduction of Udayana informatics students, it is hoped that it will be able to provide a better, complete and interactive means of introduction in providing student identity information.